ANALISIS IMPLEMENTASI SERTIFIKASI PRODUK HALAL BAGI PARA PELAKU UMKM (Studi Kasus Pelaku UMKM Di Kraton Lor) - Adimas Adinugroho; M. Sulthoni; Hendri Hermawan Adinugraha (Al-Muamalah: Jurnal Ekonomi Islam, Filantropi dan Perbankan Syariah, 2024)
The implementation of halal certification also has a significant impact on the competitiveness of MSMEs in domestic and international markets. By having halal certification, MSMEs can expand access to markets that prioritize halal products, increase consumer confidence, and create added value for their products. However, challenges such as certification costs, process complexity, and difficulties in understanding certification requirements still need to be overcome. This study highlights the importance of appropriate support from the government, non-governmental organizations and financial institutions in helping MSMEs overcome the challenges of implementing halal product certification. Training, education, and technical assistance are also needed to improve understanding and compliance with halal certification procedures. In this way, MSMEs can exploit the full potential of halal certification to increase their competitiveness in an increasingly halal-conscious market. The type of research that researchers use is a descriptive and interpretive approach to explore the phenomenon being studied thoroughly. The descriptive qualitative analysis technique is an analysis of data in the form of oral or written information that does not have the nature of numbers.